PALPEBRAL METASTASIS 11 YEARS AFTER DIAGNOSIS OF DUCTAL BREAST CARCINOMA - Calabria, André Chaves (Mastology, 2021)
Introduction: We seek to report a rare case of metastasis of infiltrating ductal carcinoma of the breast in the eyelid with a presentation 11 years after diagnosis of the primary tumor. Ocular metastasis needs to be recognized, because although it has limited survival, a timely diagnosis and treatment can significantly improve the quality of life of these patients. Case report: M.S.V., female, 59 years old, presented with locally advanced right breast cancer, clinical stage T3N1M0, with a histopathological diagnosis of infiltrating ductal carcinoma by percutaneous biopsy in 2008. Initially submitted to neo - adjuvant chemotherapy, with complete clinical and histopathological response. Then, radical mastectomy was performed with right axillary lymphadenectomy and immediate breast reconstruction associated with contralateral breast symme- trization; adjuvant radiotherapy and hormone therapy with tamoxifen. She would be a carrier of pathogenic variant het- erozygous BRCA 2, but preferred not to perform other risk-reducing therapies. Shee had a favorable evolution, with good therapeutic response, and continued to undergo periodic clinical and imaging exams, without changes. In 2019, she pre- sented right eyelid ptosis, with a diagnosis of eyelid tumor. Complementary exams with evidence of an infiltrative lesion with mild expansive effect on magnetic resonance imaging of the orbit; secondary implants in the frontal region of the skull evidenced in bone scintigraphy and magnetic resonance imaging; in addition to high AC 15.3 = 274.42. A biopsy of the eyelid lesion was performed, with histopathological results of metastatic adenocarcinoma of breast origin and an immu- nohistochemical panel with the presence of estrogen receptor, Ki67 5%, no expression of HER2 and progesterone recep - tor, in addition to the presence of GATA3. Currently under treatment with Fulvestrant. The case infers great importance, due to the rarity of the metastatic site, which indicates a poor prognosis. Furthermore, it appeared more than twice it was expected after detection of the primary tumor. Although rare, these lesions can be the first sign of systemic disease.